BACK TO THE BLUE THROUGH OCEAN FERTILIZATION- A CRITICAL APPRAISAL (International Journal of Food and Nutritional Sciences, 2022)
Ocean fertilization refers to dumping iron (as powdered iron sulphate) or other nutrients (e.g. urea) into the ocean in areas with low biological productivity in order to stimulate phytoplankton growth. In theory, the resulting phytoplankton draw down atmospheric CO2 and then die, falling to the ocean bed and sequestering carbon.Stimulation of phytoplankton production through the intentional introduction of iron fines to iron-poor areas of the ocean surface is called Iron Fertilization. This is intended at accelerating the carbon dioxide (CO2) sequestration from the atmosphere and enhancing the biological productivity.Iron is a trace element necessary for photosynthesis in plants. It is highly insoluble in seawater and in a variety of locations is the limiting nutrient for phytoplankton growth. Large algal blooms can be created by supplying iron to iron-deficient ocean waters. The algal blooms facilitate the nourishment of other organisms.The world’s oceans play a key role in keeping atmospheric carbon levels in check, largely through the work of phytoplankton. These organisms consume carbon dioxide from the atmosphere as they photosynthesize; those that aren’t eaten, as well as their waste, sink to the seafloor and take some of that carbon with them and there it can lie for hundreds or thousands of years. Since then, a number of scientists have pursued the possibility of iron fertilization as a relatively simple way to draw down carbon dioxide from the atmosphere and help in stopping climate change